Combinatory statuses of tumor stromal percentage and tumor infiltrating lymphocytes as prognostic factors in stage III colorectal cancers. Issue 3 (25th January 2022) - Jin, Hye‐Yeong; Yoo, Seung‐Yeon; Lee, Ji‐Ae; Wen, Xianyu; Kim, Younghoon; Park, Hye Eun; Kwak, Yoonjin; Cho, Nam‐Yun; Bae, Jeong Mo; Kim, Jung Ho; Lee, Hye Seung; Kang, Gyeong Hoon
Abstract: Background and Aim: Tumor stroma and tumor‐infiltrating lymphocytes (TILs) are major constituents of the tumor microenvironment, although they have different effects on the prognosis of patients with colorectal cancer (CRC). Combinatory statuses of tumor‐stromal percentage (TSP) and TILs are expected to provide more powerful prognostic information but have never been studied in CRCs. Methods: Stage III CRCs from patients ( n = 487) treated with adjuvant chemotherapy were assessed for their TSP and CD3‐TIL or CD8‐TIL densities using computer‐aided methodology. With cut‐off values set at median values for intraepithelial TIL (iTIL) and stromal TIL (sTIL) densities, CRCs were sorted into low and high iTIL or sTIL groups. CRCs were classified into five quintile (Q1–Q5) groups according to their TSP and divided into high TSP (Q5) and low TSP (Q1–4) groups. Results: The combination of CD8 iTIL density and TSP was found to be an independent prognostic parameter in multivariate survival analysis in terms of cancer‐specific survival and recurrence‐free survival. CRCs with low CD8 iTIL density and high TSP showed the worst survival. The combinatory status showed more prognostic power than CD8 iTIL density or TSP alone. Multivariate survival analysis in an independent cohort of stage III CRC validated the prognostic power of the combinatory statuses. Conclusions: The findings suggest that the combinatory status might serve as a prognostic parameter in stage III CRCs. Further research in a large‐scale cohort of patients with stage III CRC is needed to validate the prognostic power of the combinatory status.